Pivotal roles of biglycan and decorin in regulating bone mass, water retention, and bone toughness - Rui Hua; Yan Han; Qingwen Ni; Roberto J. Fajardo; Renato V. Iozzo; Rafay Ahmed; Jeffry S. Nyman; Xiaodu Wang; Jean X. Jiang (Bone Research)
Abstract Proteoglycans, key components of non-collagenous proteins in the bone matrix, attract water through their negatively charged glycosaminoglycan chains. Among these proteoglycans, biglycan (Bgn) and decorin (Dcn) are major subtypes, yet their distinct roles in bone remain largely elusive. In this study, we utilized single knockout (KO) mouse models and successfully generated double KO (dKO) models despite challenges with low yield. Bgn deficiency, but not Dcn deficiency, decreased trabecular bone mass, with more pronounced bone loss in dKO mice. Low-field nuclear magnetic resonance measurements showed a marked decrease in bound water among all KO groups, especially in Bgn KO and dKO mice. Moreover, both Bgn KO and dKO mice exhibited reduced fracture toughness compared to Dcn KO mice. Dcn was significantly upregulated in Bgn KO mice, while a modest upregulation of Bgn was observed in Dcn KO mice, indicating Bgn’s predominant role in bone. High resolution atomic force microscopy showed decreased in situ permanent energy dissipation and increased elastic modulus in the extrafibrillar matrix of Bgn/Dcn deficient mice, which were diminished upon dehydration. Furthermore, we found that both Bgn and Dcn are indispensable for the activation of ERK and p38 MAPK signaling pathways. Collectively, our results highlight the distinct and indispensable roles of Bgn and Dcn in maintaining bone structure, water retention, and bulk/in situ tissue properties in the bone matrix, with Bgn exerting a predominant influence.